Policy Agenda and Legislative Process in Legislative Institutions: A Systematic Review of the Literature and its Implications for the Indonesian House of Representatives - Rofii Zuhdi Kuniawan; Muh. Azis Muslim (Asian Journal of Social and Humanities, 2026)
Research on policy agendas and legislative processes plays a strategic role in understanding the dynamics of political representation within democratic systems. The development of literature in this field still shows limitations in thematic, institutional, and geographical scope. This research aims to systematically map the development of studies on policy agendas and legislative processes, with a particular focus on the institutional dynamics of legislative bodies within the context of representative democracy. The method used is a Systematic Literature Review combined with bibliometric analysis using the R-based Biblioshiny tool, with data sourced from the Scopus database for the period 2014–2025. The findings indicate that the study of policy agendas and legislative processes has experienced relatively stagnant growth, with dominant themes including agenda setting, legislative politics, and policy processes. The intellectual structure of the literature identifies political parties as central actors in the formation of policy agendas within legislative institutions. In terms of geographical distribution, research remains concentrated in liberal democracies in Western regions, while studies in developing country contexts such as Indonesia are still very limited. The lack of studies emphasizing the institutional role of the Legislative Body of the House of Representatives reveals a significant research gap. The results of this study are expected to enrich the literature on policy agendas by incorporating an institutional perspective from the context of developing democracies and reaffirming the importance of legislative bodies in realizing democratic political representation.